Inverter 3 Fasa 220 Volt Dengan Output Sinusoidal Frekuensi 50 Hz Menggunakan Arduino Dengan Teknik Direct Digital Synthesis - Erfan, Juna Chairul (2016)
Conversion tools DC to AC or commonly called the inverter is still needed and developed, the spotlight was the use for the home industry with constrained resources PLN to power a single phase so that when the home industry requires a source of 3 phase it will be very difficult to achieve. Therefore, it was designed inverter to convert from 12 volts to 220 volts of 3 phase with a frequency of 50 Hz with a sinusoidal waveform. This inverter serves as a good backup electricity provider in the vehicle or at home, as emergency power when utility power outages home. Moreover in the future, DC to AC inverters will play an important role in changing the DC energy from renewable energy sources solar cells into AC electrical energy that is used in everyday life, especially for 3-phase loads. The use of direct digital synthesis techniques coupled with the low pass filter is expected to reduce losses of harmony. The system of direct digital synthesis utilizing the features of the Arduino is a clock timer and output compare registers (OCR). The output of this technique is capable of forming a pure sinusoidal waveform results from these techniques will be recycled with a low pass filter so that output really smooth pure sinusoidal. Because twice the processing is expected to create a reliable inverter design with a pure sinusoidal waveform (pure sinusoidal). The results of this circuit design capable of producing average phase to phase voltage of 100 volts and amperes 0.06 A with a voltage drop of 10% when burdened. Tests using LED lamp with a power of 3 watts, 5 watts and 9 watts has been done, the lights capable of burning and output voltage of 90 volts to 110 volts depending on the load that is placed.